Hukum Jual Beli Buah Apel Yang Menggunakan Cairan Lilin Persfektif Sayyid Sabiq (Studi Kasus Pasar MMTC Kec. Percut Sei Tuan Kab. Deli Serdang) - Vikramullah, Vikramullah; Fatimah Zahara (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to examine and analyse the law of buying and selling fruits apples that use liquit wax as a preservative, focusing on the views of Sayyid Sabiq. This research is conducted using a case study conducted at Mmtc Market Subdistrict Percut Sei Tuan, Regency Deli Serdang, as a real form of the existence of this phenomenon. This type of research is empirical legal research with conceptual approach and living case study. The data is collected by interview, observation and document study methods, then the data is processed by qualitative methods with a deductive thinking approach. The findings of this study indicate that the buying and selling of fruits apples using liquit wax is not permissible or void according to Sayyid Sabiq's perspective. This is because there is an element of uncertainty or lack of clarity because the seller does not know the condition of the fruit. This research also looks at the negative side effects of using wax in the long term can cause brain cancer, leukaemia and defects in children.